2021
DOI: 10.1186/s12909-021-02903-5
|View full text |Cite
|
Sign up to set email alerts
|

The effect of learning style and general self-efficacy on satisfaction of e-Learning in dental students

Abstract: Introduction The COVID-19 pandemic has had a significant impact on education. e-Learning has been becoming most popular. Satisfaction of the student is one of important goal of e-Learning, therefore factors affecting this satisfaction should be considered extensively. This study aims to evaluate the effect of learning style and General Self-Efficacy (GSE) on satisfaction of e-Learning in dental student. Method Electronic questionnaires were sent to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 28 publications
1
23
1
1
Order By: Relevance
“…Another study showed that there was a direct relationship between individual selfefficacy and satisfaction with virtual learning [22].…”
Section: Introductionmentioning
confidence: 99%
“…Another study showed that there was a direct relationship between individual selfefficacy and satisfaction with virtual learning [22].…”
Section: Introductionmentioning
confidence: 99%
“…It is also probable that students who perceive that the regulation of their learning is externally facilitated will have a greater appreciation of the teaching process, which will once again impact their well-being. We hope in future research to explain how that comes about ( Goe et al, 2008 ; de la Fuente, 2017 ; Putwain and Pescod, 2018 ; Baherimoghadam et al, 2021 ; Bakhtiar and Hadwin, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Regulatory learning, first, facilitates students’ monitoring of their own academic performance and their satisfaction with learning. There is evidence that the gradual increase of internal and external regulation predicts increased academic confidence and decreased procrastination behaviors ( de la Fuente, 2017 ; Putwain and Pescod, 2018 ; de la Fuente et al, 2021a ); Baherimoghadam et al (2021) found that even in online teaching processes there is a significant relationship moderated between perceptions of self-efficacy (i.e., the beliefs that students have about their own capacity to organize and execute the courses of action required to achieve specific outcomes ( Bandura, 1986 ) and the level of satisfaction with the learning process.…”
Section: Introductionmentioning
confidence: 99%
“…Learning styles were used to identify students' characteristics to create homogenous and heterogeneous groups (Orsini et al, 2022). The presence of various learning styles is related to students' different abilities and individual preferences to learn (Baherimoghadam et al, 2021).…”
Section: Introductionmentioning
confidence: 99%